2019
DOI: 10.1037/int0000172
|View full text |Cite
|
Sign up to set email alerts
|

Existential isolation as a correlate of clinical distress, beliefs about psychotherapy, and experiences with mental health treatment.

Abstract: Interpersonal isolation has been implicated as a correlate of various negative psychological and psychosocial outcomes. However, less is known about how existential isolation (EI), or the feeling that no one can truly understand your subjective experience, relates to psychological maladjustment and beliefs about, and experiences with, psychosocial treatments. Representing the integration of basic social psychological science on the EI construct and applied psychotherapy-relevant research, the aim of this preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…These findings underscore the uniqueness of the existential isolation construct, as well as the importance of considering the varieties of isolation and belonging, and how they may manifest differently in groups and in individuals. In particular, people occupying a nonnormative group status appear at risk of heightened levels of existential isolation, which have deleterious psychological correlates (Constantino, Pinel, Park, 2019; Long et al, 2021). In the study that follows, we turn our attention to an additional hypothesized epistemic consequence of the existential isolation that comes with occupying a nonnormative group status: feelings of uncertainty about one’s own experiences and interpretations (Pinel, 2018).…”
Section: Discussion: Studies 1a and 1bmentioning
confidence: 99%
“…These findings underscore the uniqueness of the existential isolation construct, as well as the importance of considering the varieties of isolation and belonging, and how they may manifest differently in groups and in individuals. In particular, people occupying a nonnormative group status appear at risk of heightened levels of existential isolation, which have deleterious psychological correlates (Constantino, Pinel, Park, 2019; Long et al, 2021). In the study that follows, we turn our attention to an additional hypothesized epistemic consequence of the existential isolation that comes with occupying a nonnormative group status: feelings of uncertainty about one’s own experiences and interpretations (Pinel, 2018).…”
Section: Discussion: Studies 1a and 1bmentioning
confidence: 99%
“…In particular, basic research could focus on highlighting the key markers of clinical characteristics, processes, or scenarios under which a psychotherapist should responsively draw upon a principle of change. As one example, existential isolation —which refers to the experience of feeling that no one will ever understand one’s perspective—is a social psychological construct that has lately become of interest to clinical psychologists as they seek to better understand the development, manifestation, and treatment of internalizing problems (e.g., Constantino et al, 2019; Pinel et al, 2015). More specifically, researchers have wondered whether patients may benefit from certain kinds of therapeutic strategies that are intended to foster greater connection (e.g., “I-sharing;” Pinel et al, 2015) when they show signs of existential isolation.…”
Section: Consensus In Psychotherapy Researchmentioning
confidence: 99%
“…The EIS correlates positively, but only moderately, with measures of interpersonal isolation, including loneliness ( r = .34) and alienation ( r = .32), attesting to the notion that it assesses a qualitatively different form of aloneness (Pinel et al., 2017). Recent research has also shown that existential isolation predicts psychological health outcomes, such as depression, anxiety, and stress, and that these relationships persist when controlling for interpersonal isolation (Constantino, Sommer, Goodwin, Coyne, & Pinel, 2019; Long, Pinel, Park, Costello, & Daily, 2021).…”
Section: Introductionmentioning
confidence: 99%